Technical Efficiency of the Danish Trawl fleet: Are the Industrial Vessels Better than Others? - Niels Vestergaard; Dale Squires; Frank Jensen; Jesper L. Andersen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2002)
Technical efficiency in the Danish trawl fishery in the North Sea is estimated for 1997 and 1998 by a stochastic production frontier model. This model allows noise when the frontier and the technical efficiency is found, which for fisheries is a reasonable assumption. The results show that the production frontier can be modelled by a translog function without time effects and a technical ineffi-ciency function. The type of fishery (industrial or consumption), size of vessel (greater or lesser than 60 GRT) and year give a good explanation for the ineffi-ciency in the fleet. The average technical efficiency is estimated to be 0.82. On average, industrial vessels have a higher technical efficiency than human con-sumption vessels, and smaller vessels have higher technical efficiency than lar-ger vessels. In sum, the analysis reveals that vessel larger than 60 GRT and fishing industrial species are the most efficient.
Keywords: 330; Technical efficiency; stochastic production frontier; Danish trawl fishery; Technische Effizienz; Fischereiflotte; Dänemark